The Development of Federalism as a Concept and State-Legal Formation in the Light of an Integrative Approach - Taranova, A.E.; Antonov, E.A.; Antonova, E.L. (International Journal of Criminology and Sociology, 2022)
In the context of modern globalization, the task of clarifying the role of the federalism idea as a conceptual level of cognition in the context of the formation of new forms of state-legal education becomes urgent. The most important prerequisite here is a theoretical and methodological solution to the problem of federalism as a concept involving the consideration of its historical understanding and the solution of issues of federalism as a state-legal formation (practice) inextricably linked with the genesis of the federalism concept. Hence, the main purpose of the study is to investigate the stages of the federalism concept formation and discloses the historical features of its practical implementation. Two opposing principles of federalism (integrative and disintegrative) are defined and the promising outlook of its research from the perspective of an integrative approach is shown.